2020
DOI: 10.1159/000511226
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pressure Injury Prevention Protocol in Home Care Services on the Prevalence of Pressure Injuries in the Dubai Community

Abstract: <b><i>Background:</i></b> Pressure injuries (PIs) in the community have emerged as a health care burden in the past few years, leading to high rates of morbidity and mortality among the elderly population. There is evidence that simple risk assessment tools and protocols have reduced the prevalence of PIs considerably by shifting the focus to timely prevention and adequate management. The prevalence of PIs is high in home care setting and utilizes a major share of the organizational res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The most often investigated skin condition was melanoma and/or non-melanoma skin cancer ( n = 34) [ 22 , 23 , 26 , 48 56 , 60 , 61 , 63 , 64 , 66 , 69 , 71 , 73 , 75 80 , 82 84 , 86 , 89 , 93 , 94 , 97 , 101 ], three studies did not specify ‘skin cancer’ [ 32 – 34 ]. Different types of ‘eczema’ (including atopic dermatitis) were included in eight studies [ 30 , 31 , 33 , 34 , 46 , 65 , 88 , 91 ], pressure injuries [ 45 , 68 , 81 , 85 , 90 , 99 ] and psoriasis [ 29 , 33 , 34 , 57 , 58 , 100 ] each in six studies, and xerosis/ichthyosis in five studies [ 24 , 25 , 27 , 45 , 47 , 95 ]. Other studies focused on vitiligo [ 33 , 34 , 47 , 62 ] and parasites [ 33 , 34 , 47 , 92 ], bullous pemphigoid [ 59 , 87 , 98 ], intertrigo [ 67 , 74 ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most often investigated skin condition was melanoma and/or non-melanoma skin cancer ( n = 34) [ 22 , 23 , 26 , 48 56 , 60 , 61 , 63 , 64 , 66 , 69 , 71 , 73 , 75 80 , 82 84 , 86 , 89 , 93 , 94 , 97 , 101 ], three studies did not specify ‘skin cancer’ [ 32 – 34 ]. Different types of ‘eczema’ (including atopic dermatitis) were included in eight studies [ 30 , 31 , 33 , 34 , 46 , 65 , 88 , 91 ], pressure injuries [ 45 , 68 , 81 , 85 , 90 , 99 ] and psoriasis [ 29 , 33 , 34 , 57 , 58 , 100 ] each in six studies, and xerosis/ichthyosis in five studies [ 24 , 25 , 27 , 45 , 47 , 95 ]. Other studies focused on vitiligo [ 33 , 34 , 47 , 62 ] and parasites [ 33 , 34 , 47 , 92 ], bullous pemphigoid [ 59 , 87 , 98 ], intertrigo [ 67 , 74 ...…”
Section: Resultsmentioning
confidence: 99%
“…Table S7 (Supplementary material 5) describes details of the 14 articles answering review question 3. Four studies applied interventional designs [ 38 , 68 , 99 , 114 ]. Most articles ( n = 7) focused on interventions regarding ‘skin cancer’ (melanoma, melanoma and non-melanoma skin cancer, not specified), four on the prevention (sun protection, awareness/education campaigns) [ 35 , 36 , 64 , 115 ], two on screening [ 48 , 60 ] and one referred to both [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted in Dubai revealed a significant drop in both prevalence (9.0%) and incidence rate (6.0%) of pressure ulcers, approximately 2.0% after implementing the protocol. [ 20 ] Timely and effective skincare using oil or creams reduces the occurrences of pressure ulcers.…”
Section: Discussionmentioning
confidence: 99%